Trauma na infância é fator de risco para o tabagismo: revisão sistemática - Pereira, Karla Marcila [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Introduction: In recent years, studies have been published that identified an association between the problem of childhood trauma and smoking in adult life. Smoking is a risk factor for various diseases, including oral cancer, the aim of the study is the result of research in the literature that assesses an association between smoking addiction in adulthood and the occurrence of childhood trauma. Methods: In this systematic review, PRISMA criteria were applied, a guiding question was defined by the CEEC. Two electronic databases were used, with Pubmed / Medline and Embase, for observational studies, until January 2018, dealing with childhood trauma and smoking, with specific key braces. The analysis of the description of the studies was made based on the STROBE instrument and the quality analysis of the methodology made from the Newcastle-Ottawa school. Results: Of 2785 references obtained, 13 observational studies were separated in this journal. Data analysis was descriptive. 11 studies positively related to sexual abuse with smoking; 1 study negatively related sexual abuse with smoking; 10 studies positively related to the physical physics of smoking, 7 studies were positively related to emotional trauma smoking; 5 studies related emotional neglect with smoking; 1 studies were negatively related to emotional neglect with smoking; 4 studies related to childhood trauma. The studies had 19 to 21 points in the STROBE initiative. Still, they got 6 to 8 stars in the NOS. Conclusion: With the studies included in the review, it was possible to show that childhood trauma may be a risk factor for smoking

Nos últimos anos têm sido publicados estudos que identificaram uma associação entre a ocorrência de traumas na infância e o tabagismo na vida adulta. Visto que o tabagismo é fator de risco para diversas doenças, inclusive o câncer de boca, o objetivo desse estudo é revisar resultados de pesquisas publicados na literatura que avaliaram a associação entre o vício de fumar na fase adulta e a ocorrência de trauma na infância. Métodos: Nessa revisão sistemática foi baseado nos critérios PRISMA, a questão norteadora foi definida pelo PECO. Duas bases de dados eletrônicas foram utilizadas, sendo ela Pubmed/Medline e Embase, para estudos observacionais, até janeiro de 2018, que tratassem de trauma na infância e tabagismo, com palavras chaves específicas. A análise da descrição dos estudos foi feita com base no instrumento STROBE e da análise da qualidade metodológica foi feita a partir da escola Newcastle-Ottawa. Resultados: De 2785 referências identificadas, 13 estudos observacionais foram incluídos nessa revisão. A análise dos dados foi descritiva. 11 estudos relacionaram positivamente abuso sexual com o tabagismo; 1 estudo relacionou negativamente abuso sexual com o tabagismo; 10 estudos relacionaram positivamente abuso físico om tabagismo, 7 estudos relacionaram positivamente trauma emocional com tabagismo; 5 estudos relacionaram negligência emocional com tabagismo; 1 estudos relacionou negativamente negligência emocional com tabagismo; 4 estudos relacionaram física com trauma na infância. Os estudos tiveram de 19 a 21 pontos na iniciativa STROBE. Ainda, obtiveram de 6 a 8 estrelas na NOS. Conclusão: Com os estudos que foram incluídos nessa revisão, foi possível evidenciar que ter sofrido trauma na infância pode ser fator de risco para o tabagismo
Keywords: Tabagismo; Trauma psicológico; Revisão; Neoplasias bucais; Maus-tratos infantis; Crime sexual contra as crianças; Nicotina; Tobacco use disorder